2020
DOI: 10.3390/polym12112699
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite Materials with Poly(l-lactic Acid) and Transition-Metal Dichalcogenide Nanosheets 2D-TMDCs WS2

Abstract: Layered transition-metal dichalcogenides (TMDCs) based on tungsten disulfide nanosheets (2D-WS2) were introduced via melt processing into poly(l-lactic acid) (PLLA) to generate PLLA/2D-WS2 nanocomposite materials. The effects of the 2D-WS2 on the morphology, crystallization, and biodegradation behavior of PLLA were investigated. In particular, the non-isothermal melt-crystallization of neat PLLA and PLLA/2D-WS2 nanocomposites were analyzed in detail by varying both the cooling rate and 2D-WS2 loading. The kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 43 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…As such, it would suggest that the nanofillers provoked nucleation in both polymeric components, with the effect being more pronounced for PLLA. In contrast, 2D-WS 2 nanosheets have been shown to slow down the crystallization rate of PLLA [ 25 ]. Such differences suggest that the nanoparticle shape plays a fundamental role in PLLA crystallization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, it would suggest that the nanofillers provoked nucleation in both polymeric components, with the effect being more pronounced for PLLA. In contrast, 2D-WS 2 nanosheets have been shown to slow down the crystallization rate of PLLA [ 25 ]. Such differences suggest that the nanoparticle shape plays a fundamental role in PLLA crystallization.…”
Section: Resultsmentioning
confidence: 99%
“…In this way, Lisuzzo et al demonstrated that the chitosan coating of halloysite nanotubes driven by electrostatic interactions can be considered a suitable strategy to obtain drug delivery systems with tunable properties [ 20 ]. Of particular interest is the use of layered transition metal dicalcogenide (TMDC) nanostructures, such as tungsten disulfide (WS 2 ) and molybdenum disulfide (MoS 2 ), which are broadband semiconductors with multidimensional structural anisotropy, 0D (IF), 1D (INT), and 2D [ 21 , 22 , 23 , 24 , 25 , 26 ]. These environmentally friendly and biocompatible TMDCs nanoparticles also have demonstratable processing, performance, design, and cost advantages over nanoclays, CNTs, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, elaborate methodologies have been previously reported for the synthesis of PLA/MoS 2 -NH 2 nanocomposites [ 29 ]. In our case, the WS 2 nanosheets exhibited better dispersion and semi-exfoliated structure in the solution samples than the melt-processable counterparts [ 26 ]. The good dispersion and strong interfacial adhesion may support a significant stress transfer to reinforce the properties of PLLA nanocomposites.…”
Section: Resultsmentioning
confidence: 99%
“…In a similar manner to the 2D-WS 2 nanosheets, the addition of inorganic fullerenes (IF-WS 2 ) to polyphenylene sulfide (PPS) was also found to exert significant influence on the crystallization kinetic of PPS, but in ways unexpected for polymer nanocomposites [ 39 ]. In contrast, 2D-WS 2 has been shown to reduce the crystallization rate of melt-processable PLLA nanocomposites at any concentration [ 26 ]. This discrepancy is likely related to several factors, including the nucleation efficiency (NE) and morphology of the filler, its surface energy, roughness, and state of dispersion within the matrix as well as on the filler’s ability to form the critical nucleus [ 22 , 23 , 24 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation